PROSES IMPROVEMENT PELAYANAN KESEHATAN LANJUT USIA ( LANSIA ) DI PUSKESMAS KLAMPIS NGASEM KOTA SURABAYA - Andini Rachmawati; Sri Umiyati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2019)
The purpose of this study was to describe and analyze the Improvement Process in the Elderly Health Service at the KlampisNgasem Health Center in Surabaya City using the Donabedian Theory. The research approach used is Descriptive. With the Qualitative method, as well as data collection techniques through Observation and Interview to elderly patients directly to get an idea of how the quality of health services at the KlampisNgasem Health Center in Surabaya, especially for the care of elderly patients.The results of the research conducted by the researchers can be concluded that the research on the Improvement Process of Elderly Health Services at the KlampisNgasem Health Center in Surabaya City using the Donabedian Theory through three approaches, namely the structural approach (input), the process approach, the outcome approach (output ) found two indicator that become service priority that is Service Statement or statement of ability and obligation of organizer to perform service in accordance with service standard and Service Time that is the time period needed to finish all service process from each service type.